What happened to collective bargaining during the great recession? - Jelle Visser (IZA Journal of Labor Policy, 2016)
Collective bargaining over labour conditions between unions and employers is a key labour market institution in democratic societies, guaranteed by international and national law. Its coverage, organization and impact have varied over time and across countries. Inclusive bargaining, conducted by employers' associations with a mandate to bargain, and supported by the state, received a strong impulse during the interwar Depression. In the Great Recession a more exclusive version based on enterprise bargaining appears to have been favoured by governments and international agencies. How this relates to changes in bargaining coverage, multi-employer and multi-level bargaining, rules on extension and opening clauses is the subject of this paper, which surveys developments in 38 OECD and EU countries. A distinction is made between long-term and crisis-related changes, and between regulatory and non-regulatory changes during the Great Recession.
Keywords: J52; J53; J51; J58; 330; Collective bargaining; Labour-Management Relations; Trade Unions; Public Policy